Analysis of Key Performance Identification at Splash Hotel - Pertiwi, Adilla; Widanti, Afrima (Student Journal of Business and Management, 2023)
This research was conducted to examine this research with the research objective of knowing and analyzing the relevant Key Performance Indicators (KPI) applied to the Splash Hotel using the Performance Prism method. This type of research is descriptive research to analyze relevant KPI applied to the Splash Hotel using the Performance Prism method. The population and sample in this research is the General Manager of the Splash Hotel, namely Mr. Dawn. Content Analysis is a qualitative research technique that emphasizes the accuracy of communication content, meaning in communication content, interpretation of symbols, and understanding symbolic interactions that occur in communication. The results of the research show that the Splash Hotel KPI using the Performance Prism method is not optimal because: 1) The KPI seen from Splash Hotel Stakeholders is not optimal. This is because Splash Hotel has not been able to increase the number of purchases it needs from suppliers, superiors' attention to employees is still low and Splash Hotel's support for the community around the hotel is still low, 2) KPI seen from Stakeholder Contribution Splash Hotel is not optimal. This is because Splash Hotel's provision of incentives to employees is still low, superiors' appreciation for employees is still low, and the number and quality of local employee recruitment is still low, 3) KPI seen from Splash Hotel's Strategy is not optimal. This is because the Splash Hotel strategy in gaining profits and hotel development strategies is still lacking, and the provision of guidance and training to employees is low, 4) KPI seen from the Splash Hotel Process is not optimal. This is because the strategy in the partnership and environmental development program around the Splash Hotel is still low and 5) the KPI seen from the Capability of the Splash Hotel is not optimal. This is because the accuracy of payments to raw material suppliers is still low or not on time.